Auditoría informática al sistema contable y su incidencia en la confiabilidad de la información financiera, empresa CODIHE-S.A, período 2018. - Carla Pamela, Panchi Herrera (2021)
The main objective of this research project is to develop a computer audit of the accounting system to determine its impact on the reliability of the financial information of the company CODIHE SA, during the period 2018. For which this work has been divided into four chapters: In the first chapter, the referential framework is detailed, the research problem was identified, the hypothesis was formulated, and in general what will be achieved with the present research was defined. The second chapter details the theoretical framework and the conceptual framework on the company and the variables both independent and dependent on the investigation. The third chapter presents the methodological framework, the method used is deductive, the type of research applied is documentary and field, the design is non-experimental and has two approaches; qualitative and quantitative, with regard to the population, the entire population has been taken into account to obtain information, for which reason a sample was not applied. In chapter IV the three phases of the computer audit are developed: In the planning, the previous visit, the interview, the internal control of the company was evaluated using the COSO III model. During the execution, the audit tests were applied, indicators of efficiency, efficacy and information security were developed, the findings were determined, and finally, in the results communication phase, the final computer audit report is prepared.